Preoperative prealbumin-to-fibrinogen ratio predict Survival Outcomes in hepatocellular carcinoma patients after hepatic resection - haixi, Yan; shuaishuai, chen; qiong, Yang; linling, cai (Journal of Medical Biochemistry, 2022)
Objective: This study aims to evaluate the clinical application of preoperative prealbumin-to-fibrinogen ratio (PFR) in the clinical diagnosis and prognostic value of hepatocellular carcinoma (HCC) patients. Methods: The clinical and laboratory data of 269 HCC patients undergoing surgical treatment from January 2012 to January 2017 in Taizhou Hospital were retrospectively analyzed. The Cox regression model was used to analyze the correlation between PFR and other clinicopathologic factors in overall survival (OS) and disease-free survival (DFS). Results: Cox regression analysis showed that PFR (hazard ratios [HR] = 2.123; 95% confidence interval [95% CI], 1.271–3.547; P = 0.004)was independent risk factors affecting the OS of HCC patients. Furthermore, a nomogram was built based on these risk factors. The C indices statistics for the OS nomogram was 0.715. Conclusion: Nomograms based on PFR can be recommended as the correct and actual model to evaluate prognosis for patients with HCC.
Keywords: hepatocellular carcinoma; prealbumin-to-fibrinogen ratio; survival analysis; Nomogram